PENGARUH PENGGUNAAN KNEE SUPPORT TERHADAP PENGURANGAN NYERI LUTUT PADA PEMAIN BOLA TENIS - Utomo, Prasetyo Catur; Akbar Nabila, Iltizam; fatati, muhibbah (Medical Journal of Nusantara, 2025)
Background: People of all ages frequently have knee pain, which frequently strikes unexpectedly after an injury or physical activity. Tennis players may suffer from degenerative illnesses, injuries, or excessive and repeated motions that cause knee pain. Using a knee support with an open patella design is one way to manage pain. The purpose of this study was to ascertain whether using knee supports can help tennis players with their knee problems. Methods and Subjects: This study included a one-group pre-test and post-test design, a quantitative research approach, and a quasi-experimental methodology. Purposive sampling was used in the sample process, and 13 respondents satisfied the inclusion and exclusion criteria. Before and after utilizing the knee support—which is only worn during play—pain levels were assessed using a Visual Analog Scale. results: The Wilcoxon test got results with a value of 0.001, indicating a significant effect because P <0.05. In conclusion, this study shows how well knee support helps to reduce knee pain in tennis players.